A Case Study of Impact of Aquatic Plants on Pond Water Quality - PENG Ailing; GU Zhun; HUANG Jinbai; ZHANG Qin; NI Tao; TAO Siji (Renmin Zhujiang)
Aquatic plants play an important role in regulating the water quality of ponds.To reveal the effects of the aquatic plants on pond water quality,taking a specified pond,which is located inside the Jiangyanglu South Campus of Yangzhou University,as the study area,this paper observes the water quality parameters such as phycobilin chromophore (Phyco),water temperature (WT),dissolved oxygen (DO),pH and electrical conductivity (EC) of pond areas with aquatic plants or without aquatic plants,analyzes the temporal variation characteristics of each water quality parameter by the methods of coefficient of variation,single factor water quality identification index and multiple linear regression model,and evaluates the effects of the aquatic plants on water quality.The results indicate that:①WT,DO of the aquatic plant area are lower than those of the non-aquatic plant area during the research period;②The water is alkaline,and the pH of the non-aquatic plant areas is generally higher than that of aquatic plan area;③The fluctuation degree of each parameter in the non-aquatic plant area is larger than that of the aquatic plant area in the same period,and the variation weight of water quality parameters in the two areas from high to low is DO>WT>EC>pH;④The time for water quality in the non-aquatic plant area reaching Class Ⅲ accounts for 67.7% of the research period,and the water quality of the non-aquatic plant area is better than that of the aquatic plant area;⑤During the study period,the impact of WT on DO in the non-aquatic plant area and the aquatic plant area was inconsistent,while the impact of Phyco and pH on DO is more significant than that of WT.